Hormonally induced gonadal maturation in eels, Anguilla bicolor bicolor McClelland 1984 with the use of Pregnant Mare Serum Gonadotropin, anti dopamin, and recombinant Growth Hormone - Hadra Fi Ahlina; Agus Oman Sudrajat; Tatag Budiardi; Ridwan Affandi (Jurnal Iktiologi Indonesia, 2015)
The aim of this study was to evaluate the effect of Pregnant mare serum gonadotropin (PMSG), Anti-Dopamine (AD) and Recombinant growth hormone (RGH) through the injection technique on gonadal development of eel (Anguilla bicolor bicolor). The experimental was arranged in completely randomized design with five treatments of hormone combination, namely P10A combination hormone (10 IU PmsG + 0.1 mgL-1 AD), P10B (10 IU PMSG + 0.1 mgL-1 AD + 10 ug RGH), P20A (20 IU PMSG + 0.1 mgL-1 AD), P20B (20 IU PMSG + 0.1 mgL-1 AD + 10 ug RGH), and PK (negative control). In each treatment, a total of 20 fish individuals used as replicates and the hormonal induction was conducted every week for eight weeks of the rearing period. Specific growth rate (SGR), hepatosomatic index (HSI), go-nadosomatic index (GSI) and an index of the eye (IM) were observed. The results showed that the P20A treatment increased spermatogenesis and the value of GSI (2.291±0.278%) at 4-6 weeks after injection. This result was higher than P20B (2.134±0.265%), P10B (2.065±0.201%), P10A (2.037±0.105%), and PK (1.937±0.050%). The value of HSI on the P20a treatment (1.188±0.091 %) was higher than other treatments. The highest value of SGR (0.514±0.062%) was found in the P20B, whereas the lowest value (0.052±0.027%) was found in the PK. Thus, the combination of pMsG, AD and RGH hormones can stimulate the development of testicular of eel with body weight 140 to150 g, and stimulate the growth of 0.514 % during the six-weeks rearing period. Abstrak Penelitian ini bertujuan mengevaluasi penggunaan hormon Pregnant Mare Serum Gonadotropin (PMSG), Anti Dopamin (AD) dan Recombinant Growth Hormone (rGH) melalui teknik penyuntikan terhadap pematangan gonad ikan sidat (Anguilla bicolor bicolor). Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) dengan lima perlakuan kombinasi hormon yaitu 10 IU PMSG + 0,1 mgL-1 AD (P10A), 10 IU PMSG + 0,1 mgL-1 AD + 10 ^g rGH (P10B), 20 IU PMSG + 0,1 mgL-1 AD (P20A), 20 IU PMSG + 0,1 mgL-1 AD + 10 ^g rGH (P20B), dan PK (kontrol). Pada setiap perlakuan, sebanyak 20 ekor ikan digunakan sebagai ulangan individu dan sampling dilakukan setiap minggu selama delapan minggu masa pemeliharaan. Parameter yang diamati meliputi nilai laju pertumbuhan spesifik (LPS), indeks he-patosomatik (IHS), indeks gonadosomatik (IGS) dan indeks mata (IM). Hasil penelitian menunjukkan bahwa perlakuan P20A menyebabkan perkembangan spermatogenesis dan meningkatkan nilai IGS tertinggi (2,291±0,278%) pada minggu ke empat hingga ke enam setelah penyuntikan dibandingkan perlakuan P20B (2,134±0,265%), P10B (2,065± 0,201%), P10A (2,037±0,105%) dan PK (1,937±0,050%). Nilai IHS pada perlakuan P20A (1,188±0,091%) lebih tinggi dibandingkan dengan perlakuan lainnya. Nilai LPS tertinggi ditemukan pada perlakuan P20B (0,514±0,062 %) dan te-rendah pada perlakuan Kontrol (0,052±0,027%). Nilai IM juga meningkat pada perlakuan P20B (10,599±2,372) seiring dengan bertambahnya bobot tubuh dan terendah pada perlakuan PK (7,189±0,217). Kombinasi hormon PMSG, AD dan rGH dapat merangsang perkembangan testis ikan sidat ukuran 140-150 g serta memacu pertumbuhan 0,514 %.